Artificial bee colony algorithm with scanning strategy for the periodic vehicle routing problem. (June 2013) - Yao, Baozhen; Hu, Ping; Zhang, Mingheng; Wang, Shuang
The periodic vehicle routing problem (PVRP) is an extension of the vehicle routing problem (VRP). Because it extends the single delivery period to a T -day period ( T > 1), PVRP has strong theoretical and practical significance. Since PVRP is an embedded VRP, it is more complex and difficult compared with the general VRP. In this paper, the bee colony algorithm is used to solve the PVRP. To improve the performance of this algorithm, multidimensional heuristic information and a local optimization based on a scanning strategy are used. At the end of this paper, the algorithm is tested by some well-known examples. The results show that the proposed improved bee colony algorithm is a powerful tool for solving the PVRP. It also shows that these two kinds of strategies can significantly improve the performance of the algorithm.